Computational Wind Engineering of a Mast-supported Tensile Structure - Pool Blanco, Sherly Joanna; Hincz, Krisztián (Periodica Polytechnica Civil Engineering, 2022)
The Computational Fluid Dynamics (CFD) analysis of wind actions on a cube and on the hyperbolic surface of a mast-supported tensile structure is presented. As standard in Computational Wind Engineering (CWE) the models were analyzed in incompressible fluid flow. For the CWE study, the Reynolds-Averaged Navier-Stokes (RANS) equations were solved with two of the most widely used turbulence models, Realizable k−ε and SST k−ω. The validation of the CWE models included the comparison of the numerically determined pressure coefficient fields with existing Wind Tunnel test (WT) results. The membrane forces and the displacements of the membrane roof were calculated by the Dynamic Relaxation Method (DRM), corresponding to the different (CWE and WT) pressure coefficient fields of the tensile roof. In addition to the pressure coefficients, the membrane force and the displacement fields and their significant values were also compared. It is presented that both turbulence models provide a suitable solution; the pressure coefficients and the membrane forces are also acceptable approaches to the experimental results.